Laser removal of biofilm from Carrara marble using 532 nm: The first validation study. (December 2018) - Mascalchi, Marta; Osticioli, Iacopo; Adriana Cuzman, Oana; Mugnaini, Sonia; Giamello, Marco; Siano, Salvatore
Highlights: Laser treatment of outdoor biodegraded marble artifacts is still an open issue. CF-PAM imaging technique allows optimizing the laser treatment process. Photosynthetic pigments of biodeteriogens enhance the absorption of 532 nm radiation. This is the first validation study of laser biodeteriogens removal at 532 nm. Abstract: Here we report the first extensive validation study of laser removal of biodeteriogens from marble. The work was carried out on the Speranza, monumental sculpture of the 19th century placed inside the English Cemetery in Florence. The statue was covered by diffuse greenish and black-grayish species due to the biological growth, a mix of cyanobacteria, algae and fungi classified as biofilm. Optical microscopy, culture-based methods and CF-PAM imaging (Pulse Amplitude Modulated fluorometry of the Chlorophyll Fluorescence) were used to characterize the biodeteriogens. Laser technique was proposed as an efficient alternative for the traditional cleaning methodologies. Preliminary trials were performed using different wavelengths and pulse durations. The optimization of the laser parameters was performed considering the results obtained from the stratigraphic layers observations of the cross-sections of the stone material and real time CF-PAM imaging of the phototrophic presence. The study allowed improving, planning and accomplishing of the laser cleaning treatment of the whole statue.